Fórum de alfabetização leitura e escrita (FALE) Flor do Grão Pará: narrando histórias entre ensino, pesquisa e extensão - COSTA, Andréa Queiroz (2024)
The main objective of this monograph is to analyze the narrative of the guests and participants of the Reading and Writing Literacy Forum (FALE) Flor do Grão Pará, which was my research object, during the Integrated Degree in Science, Mathematics and Languages at the Federal University from Pará, I also analyze my academic trajectory and my encounter with the research object. The methodology applied was a narrative research that allowed me to understand the meanings and characteristics of the literacy process and reflect on teaching practices through different applications, presented in the five Forums presented in this monograph. At first, I present the Reading and Writing Literacy Forum, as a space for initial and continuing education, the creation of FALE Flor do Grão Pará and my encounter with research. In a second moment, I present, narrate and analyze the TALKS that occurred in the years 2018 and 2019, it is noteworthy that it was possible to reflect the teaching practice on the different techniques applied in meetings and in the daily life of classes at the university. Therefore, it is essential to discuss in spaces of initial and continuing education, which allow and contribute to teacher professionalization.